2016
DOI: 10.1128/aac.00544-16
|View full text |Cite
|
Sign up to set email alerts
|

A Telomeric Cluster of Antimony Resistance Genes on Chromosome 34 of Leishmania infantum

Abstract: The mechanisms underlying the drug resistance of Leishmania spp. are manifold and not completely identified. Apart from the highly conserved multidrug resistance gene family known from higher eukaryotes, Leishmania spp. also possess genus-specific resistance marker genes. One of them, ARM58, was first identified in Leishmania braziliensis using a functional cloning approach, and its domain structure was characterized in L. infantum. Here we report that L. infantum ARM58 is part of a gene cluster at the telomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 65 publications
0
25
0
Order By: Relevance
“…The sensitivity of cosmid-based functional screening was enhanced by its recent coupling to next-generation sequencing in an approach termed Cos-Seq 124 . The proportion of parasites with cosmids providing a selective advantage is expected to rise with increasing drug pressure, and these can be tracked and quantified at each drug increment by Illumina sequencing 124 , 125 . Thus, the dynamics of cosmid enrichment can be followed over the entire course of selection instead of being monitored only at endpoint.…”
Section: Exploiting Copy Number Variations For Understanding Drug Modmentioning
confidence: 99%
“…The sensitivity of cosmid-based functional screening was enhanced by its recent coupling to next-generation sequencing in an approach termed Cos-Seq 124 . The proportion of parasites with cosmids providing a selective advantage is expected to rise with increasing drug pressure, and these can be tracked and quantified at each drug increment by Illumina sequencing 124 , 125 . Thus, the dynamics of cosmid enrichment can be followed over the entire course of selection instead of being monitored only at endpoint.…”
Section: Exploiting Copy Number Variations For Understanding Drug Modmentioning
confidence: 99%
“…Interestingly, the increased levels of thiols and MRPA mRNA in LgSbR also correlates with its higher sensitivity to BSO compared to its WT counterpart, in agreement with the observation of Moreira et al (2013) for L. braziliensis . Whether the efflux transport also involves an exocytosis or a secretion pathway, as previously hypothesized (Legaré et al, 2001; Manzano et al, 2013; Perea et al, 2016; Tejera Nevado et al, 2016), still need to be investigated. In LbSbR, the effect of probenecid on the Sb efflux is also consistent with a MRP-type transporter, however, no increase in gene expression of the potential transporters MRPA, LABCI4 and ARM58 was observed (Figure 1).…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, ARM58 was found to be localized near the flagellar pocket hints but, contrary to LABCG2 and LABCl4, it did not seem to mediate energy-dependent transport activity. Indeed, ARM58 is part of a subtelomeric cluster comprising the neighboring genes ARM56 and HSP23, which confers antimony resistance by inducing exosome-mediated secretion (Tejera Nevado et al, 2016). Using a new approach called Cos-Seq—that combines functional cloning and massive next-generation sequencing, Gazanion et al (2016) have confirmed the up-regulation of ARM58 in laboratory-selected antimony-resistant L. infantum (Gazanion et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A competition assay with full-length or truncated derivatives of the cosmid insert validated ARM58 as a SbIII resistance gene. A more recent study performed by the same group with cosmid-transfected L. infantum extended this finding to the neighboring genes and defined a cluster of three genes, ARM58, ARM56 (previously named ARM58rel), and HSP23 at the telomere of the chromosome 34 that confer increased resistance of intracellular amastigotes against SbV (Tejera Nevado et al, 2016 ). Using a L. infantum cosmid library, the same team revealed a protein termed P299 that conferred increased resistance of intracellular amastigotes to MIL and reduced promastigote sensitivity to MIL and SbIII, but not pentamidin (Choudhury et al, 2008 ).…”
Section: Cosmid-based Functional Genetic Screening In Leishmentioning
confidence: 97%